KARAKTERISTIK KETEKNIKAN TANAH DAN HUBUNGANNYA DENGAN PENGEMBANGAN WILAYAH DI KAWASAN PENGEMBANGAN TERPADU - JATINANGOR, KABUPATEN SUMEDANG, JAWA BARAT - -, Zufialdi Zakaria; -, Yuyun Yuniardi; -, Irvan Sophian (Fakultas Teknik Geologi Universitas Padjadjaran, 2007)
Soil in research areal consist of CH (clay, high plastisitas) and MH. (silt, high plastisitas). Soil activity at area of Jatinangor is vary from low activity to high. But in general soil activity is hidh-medium. Activity number by Seed is A = 0.40 until 0.86 with nature mineral of kaolinitic until ilitic. Stability of slope can be designed as according to slope-stability design. At exposition slope, slope with angle 45o, two terrace and ground water level at - 2 M, high of slope 5 M and level off 5 M, Safety Factor = 2.094. Soil bearing capacity for square, circular & continuous foundations have medium-high activity show relationship that: Increasing of soil activity value cause decreasing of value of soil bearing capacity. Safety Factor of slope and soil bearing capacity is very supporting of environmental aspect in Jatinangor development area. Geological evaluation of development area is required to study both aspect (slope safety and bearing capacity).Environmental management is required before the rains arrive, because ground water rate will increasing at rainfall condition. It is required to manage negative impact. It is required to anticipate or eliminated its impact, or generating positive impact to be managed by improving it. Environmental monitoring is required to be instructed as anticipatory effort of damages or effect of negative impact.